(untitled) (Annals of Medical Research, 2025)
Aim: Differential diagnosis of borderline ovarian tumors (BOT) and malignant lesions with MRI is of great importance in terms of recognizing the chance of fertility preserving surgery. We aimed to describe and compare the MRI imaging findings and morphologic features of borderline and malignant ovarian tumors. Materials and Methods: Patients who underwent pelvic MRI due to adnexal mass between 2019 and 2024 in the Radiology departments of two centers have been screened. Thirty-six lesions from 34 patients with BOT were identified and compared with the randomly selected 20 malignant adnexal tumors in 19 patients. Morphological features of lesions, contrast enhancement pattern, Apparent Diffusion Coefficients values, presence of ascites and peritoneal implants were evaluated for each lesion. Results: Type 3 contrast enhancement pattern was reported in 8% of BOTs, and 26% of the malignant tumors. No significant difference was observed between BOT and malignant lesions in terms of contrast enhancement pattern (p = 0.274). In patients with BOTs, our rate of differentiating the ipsilateral ovary was higher than in malignant patients. Ipsilateral ovary was not discriminated in 25 (69.4%) of the BOTs, and 18 (90%) of the malignant lesions, with a borderline statistical significance (p = 0.075). Although the papillary lesions were commonly borderline and big-amorph lesions were commonly malignant, the difference did not reach statistical significance (p = 0.078). Conclusion: Presence of solid tissue and the type of solid component are the most prominent features for the distinction of BOTs and malignant lesions. Time-intensity curves may provide additional information.